Development of Bioplastic Films from γ − Irradiated Kithul (Caryota urens) Starch; Morphological, Crystalline, Barrier, and Mechanical Characterization. (2nd March 2021) - Sudheesh, Cherakkathodi; Sunooj, Kappat Valiyapeediyekkal; Jamsheer, Vattaparambil; Sabu, Sarasan; Sasidharan, Abhilash; Aaliya, Basheer; Navaf, Muhammed; Akhila, Plachikkattu Parambil; George, Johnsy
Abstract: Important properties of bioplastic film made from γ − irradiated kithul starch such as crystalline, morphological, mechanical, and barrier properties are studied. The films are made from native and irradiated kithul starch using the casting method. Relative crystallinity is higher for the film made from irradiated kithul starch. The film made from 100 kGy irradiated starch shows the highest relative crystallinity (2.26%) among the starch films. The film prepared from irradiated kithul starch exhibits lower water vapor permeability (WVP). The solubility of film made from irradiated starch decrease with an increase in irradiation dose. Irradiation of starch cause higher surface compactness, which decrease the oxygen permeability of the films. The decrease in WVP and oxygen permeability indicates the improved barrier properties of films made from irradiated starch. Mechanical properties increase in films made from irradiated kithul starch. Moreover, it shows lower surface roughness as compared with native starch film. The research reveals that films made from γ − irradiated kithul starch exhibited better mechanical and barrier properties due to their higher crystallinity and surface homogeneity. Abstract : Irradiation increases the relative crystallinity of bioplastic films. Irradiated kithul starch films show higher tensile properties. γ‐Irradiation increases barrier properties of bioplastic films.